Understanding of MIS Specialty in Jordan: Empirical Investigation from Students’ Perspective - Mansi, Ibrahim N; Rababah, Khalid Ali (Journal of Asian Business Strategy, 2015)
The Management Information Systems (MIS) specialty plays a crucial role in the management and application of information technology and information systems in organizations. Consequently, there is an increasing demand for qualified graduates in the MIS specialty. However, there is a lack of the understanding of the MIS specialty among the Jordanian students. Therefore, the aim of this study is to examine the factors affecting students’ understanding of MIS specialty in the Jordanian universities. The study followed quantitative research approach which is survey-based using a questionnaire. Around 250 questionnaires were distributed randomly to MIS students at the private universities in northern region in Jordan and 194 valid questionnaires were received. Multiple regression technique was deployed for the data analysis. The results revealed that the students’ capabilities, the students’ beliefs, and the students’ expectations were significantly influencing the students’ understanding of MIS specialty. Moreover, the results indicated that the developed model explains 40.5% of the variance in the students’ understanding of MIS specialty. Practically, students understanding of the MIS will enable them to market the specialty in Jordanian market.